2020
DOI: 10.3390/ma13030798
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Reinforced with Inconel 718 Particles Prepared Ex Situ—Microstructure and Properties

Abstract: Magnesium samples reinforced with 0.7, 1.4, and 2.4 vol.% of Inconel 718 particles were prepared using a disintegrated melt deposition technique followed by hot extrusion. Mechanical properties, thermal expansion, and damping were studied with the aim of revealing the particle influence on the microstructure, texture, tensile and compressive behavior, thermal expansion coefficient, and internal friction. The flow stresses are significantly influenced by the test temperature and the vol.% of particles. A substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Therefore, the improvement in the hardness values could be related to the combination of refinement of the α-Mg grain size caused by the dynamic recrystallization via FSP along with the pinning effect of WC nanoparticles. The variation in the thermal expansion coefficients between different materials, such as AZ91 Mg alloy (26 x 10 -6 K -1 ) [30] and WC particles (~5.5x10 -6 K -1 ) [31], results in an increment in the dislocation density [32]. S. Graça et al [33] showed that the increase in the dislocation density created a hindrance to deformation resulting in an increase in the hardness.…”
Section: Hardness Profilementioning
confidence: 99%
“…Therefore, the improvement in the hardness values could be related to the combination of refinement of the α-Mg grain size caused by the dynamic recrystallization via FSP along with the pinning effect of WC nanoparticles. The variation in the thermal expansion coefficients between different materials, such as AZ91 Mg alloy (26 x 10 -6 K -1 ) [30] and WC particles (~5.5x10 -6 K -1 ) [31], results in an increment in the dislocation density [32]. S. Graça et al [33] showed that the increase in the dislocation density created a hindrance to deformation resulting in an increase in the hardness.…”
Section: Hardness Profilementioning
confidence: 99%
“…With the strong bond between Nickel and Aluminium at an elevated temperature, NiAl can efficiently contend with ceramics or superalloys due to its remarkable characteristics at high temperatures and good strength. In comparison to the traditional nickel-based superalloys, the NiAl-based alloy has demonstrated better thermomechanical characteristics and good corrosion, wear, and creep resistance [1][2][3][4][5][6]. A recent study has focused on Nickel-Aluminide, an intermetallics; comprising Aluminium and Nickel.…”
Section: Introductionmentioning
confidence: 99%
“…This bond has generated outstanding properties at an extreme temperature and good strength that could effectively compete with superalloys and ceramics. The NiAl-based alloy has shown superior thermomechanical properties, excellent corrosion, wear, and creep resistance compared to the conventional nickel-based superalloys [1][2][3][4][5][6]. Nickel-aluminide is an intermetallic compound containing aluminium and nickel and has been the focus of recent researchers.…”
Section: Introductionmentioning
confidence: 99%